Influence of Primary School Teachers’ Motivation on Pupils’ Academic Performance in Federal Capital Territory Abuja Nigeria - Saheed Kolawole Wahab (Journal of Early Childhood Development and Education, 2026)
Background: Teachers’ motivation is widely recognized as a critical factor influencing pupils’ academic performance, particularly at the foundational level of education. In Nigeria’s Federal Capital Territory (FCT), persistent challenges such as irregular salary payment, inadequate remuneration and limited opportunities for professional development have raised concerns about their implications for pupils’ academic outcomes in primary schools. Objective: This study examined the influence of primary school teachers’ motivation on pupils’ academic performance in FCT Abuja, Nigeria. Specifically, it investigated the relationships between teachers’ motivation, prompt payment of salary, remuneration, professional development and pupils’ academic performance in public primary schools. Methods: A descriptive survey research design was adopted. The population comprised 12,627 primary school teachers across the six Area Councils of FCT Abuja. Through a multistage sampling technique, 300 primary school teachers were selected. Data were collected using a structured questionnaire and a pro-forma. Pearson Product Moment Correlation was used to analyse the data at the 0.05 level of significance to test four null hypotheses. Result: The findings revealed significant positive relationships between teachers’ motivation, prompt payment of salary, remuneration, professional development, and pupils’ academic performance in primary schools in FCT Abuja, Nigeria. Conclusion: The study concluded that teachers’ motivation and related welfare factors are critical determinants of pupils’ academic performance. It therefore recommends that Area Council Chairmen prioritize teachers’ motivation, ensure prompt payment of salaries, improve remuneration, and strengthen professional development opportunities. In addition, the FCT Administration should transfer the management of primary school teachers from the Local Education Authorities (LEAs) to the Universal Basic Education Board (UBEB) for more effective administration.